A Multi-Agent Based Simulation to Support the Digital Assistant for Participatory Public Management - Patto, Vinícius Sebba; Oliveira, Ivanilton José de; Lewkovicz, Zach; Seghrouchni, Amal El Fallah (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA), 2013)
In this paper, we introduce our current research project geared towards a computer-based support for constructing democratic governance in urban scenery, in order to promote citizens’ involvement on public management. The goal of this research is to help public managers to choose socio-environmental aspects to invest governmental funds in order to diminish most popular citizens’ complaints. In order to achieve this goal, we take in consideration users’ feelings about some socio-environmental aspects and the possibility of correlations between some of these aspects, time, and place. There are three main components in our project: a responsive web application coupled with a mini-station to collect socio-environmental data, a miner agent, and a decision support agent. Our approach combines techniques such as: multi-agent systems, knowledge discovering in database, sensor networks, and multi-criteria analysis. Some of these components were tested and our proof of concept demonstrated the feasibility and the potential of our approach.